Slovakia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This update of the 1995 CPAR is based on the September 1999 PPA and the findings of the Bank CPAR mission to Slovakia in November 1999. The 1999 Public Procurement Act (PPA) is an improvement upon the previous PPAs in some respects, including the creation of an OPP, more detailed and clear procurement procedures, accreditation of procurement professionals, introduction of the Public Procurement Bulletin and expanded bid protest resolution procedures. However, it is the Bank's view that, although the procurement methods in the 1999 PPA comply with EU Directives, some of these methods lack transparency and may not result in efficient and competitive procurement. The PPA provides for four procurement methods: open tendering, restricted tendering, negotiated tendering with prior notification; and negotiated tendering without prior notification. While open tendering includes transparent procedures which will lead to competitive and economic procurement, the PPA does not include appropriate criteria for the use of restricted tendering, such as the availability of a limited number of suppliers, response to natural disasters, etc. Similarly, the negotiated procurement with prior notification method lacks transparency and gives excessive discretion to the contracting authority. In order to improve the transparency of the negotiated procurement with prior notification method, it is recommended that the conditions for its use should be brought more into line with those contained in the European Union Supplies Directive and that, where such conditions of use are not met, Open or Restricted Tendering should be employed. The Bank also recommends strongly, as it did in the past, the inclusion in the PPA of separate provisions relating to procurement of consultants' services in future amendments to the PPA. Other recommendations include improving procurement planning by providing information about budgetary allocations early in the budgetary cycle; establishing contracting authorities of a permanent procurement committee responsible for decision making and for providing oversight; introducing a formal code of ethics for government employees to improve their accountability in procurement; continuous training of the staff of contracting authorities in procurement; updating of the procurement guidelines and standard bidding documents; collecting and disseminating best procurement practices to contracting authorities; maintaining dialogue with the private sector to keep suppliers, contractors and consultants informed of the requirements of the PPA and of improvements in the procurement system.